Anticorrosion agents in different forms- A review - Hussein Idrees Ismael; Rawaa Z.Jafat; Shaker Salih Baha; Hayfaa A.mubarak (Zien Journals, 2022)
An enormous amount of annual research has been conducted on corrosion inhibitos, including their synthesi s or extraction, as well as the mechanisms of classification and inhibition. For a long period of time, the corrosion and damage caused by it in the majority of industrial operations resulted in significant losses and expensive expenses. The ability of such compounds to adsorb on the metal/solution interface isoften attributed to their capacity t o stop corrosion. The mechanism of electrochemical corrosion and the surface area accessible for the proces s are both altered as a result of an inhibitor's contact with a metal surface.
Keywords: corrosion inhibitors; corrosion mechanism; inhibitor types